Enhanced Blood Supply Through Lower Body Negative Pressure During Slow-Paced, High Load Leg Press Exercise Alters the Response of Muscle AMPK and Circulating Angiogenic Factors - Parganlija, Dajana; Gehlert, Sebastian; Herrera, Frankyn; Rittweger, Jörn; Bloch, Wilhelm; Zange, Jochen (Frontiers in Physiology, 2020)
Lower body negative pressure (LBNP) is an established method of simulating the gravitational effects of orthostasis on the cardiovascular system during space flight or at supine body position on Earth. We hypothesized that LBNP added onto leg press exercise would promote leg muscle perfusion, stimulate oxygen consumption, and modify acute molecular responses. Eighteen subjects performed fifteen slow-paced concentric (4 s) and eccentric contractions (4 s) without or with 40 mmHg LBNP. Force corresponding to 6% of the one repetition maximum (1-RM) at knee flexion gradually increased to 60% 1-RM within the first half of the range of motion, thereafter remaining constant. AMPK and P-AMPK protein expression was determined in biopsies of vastus lateralis. Venous blood samples were used to measure angiogenic factors. Physiological responses to LBNP included an elevated EMG-amplitude (p < 0.001), higher heart rate and doubling of the cardiac output compared to control. Muscle total hemoglobin was increased by around 20 µmol / l vs. control (p < 0.001), accompanied by decreasing tissue oxygen saturation and elevated oxygen uptake (p < 0.05). MMP-2 levels were reduced, and the ratio of P-AMPK to AMPK elevated after exercise with LBNP (p < 0.05). MMP-9 similarly increased in both groups, whereas endostatin was only elevated in the control group (p < 0.05). Our results indicate facilitated peripheral blood supply and higher oxygen exploitation leading to activation of the energy sensor AMPK and differential regulation of angiogenic factors involved in muscle tissue remodeling and capillary growth. Simulating orthostasis with LBNP might promote beneficial structural adaptations of skeletal muscles during resistance exercise and contribute to future exercise countermeasures achieving increased muscle strength and endurance during space flight.